1998
DOI: 10.1542/peds.102.s3.512
|View full text |Cite
|
Sign up to set email alerts
|

Adult Height in Children With Growth Hormone Deficiency Who Are Treated With Biosynthetic Growth Hormone: The National Cooperative Growth Study Experience

Abstract: Objective. To determine whether the height gain during puberty in children with growth hormone deficiency (GHD) who are treated with biosynthetic growth hormone (GH) is similar to that in otherwise healthy children with delayed bone ages and whether the height standard deviation score (SDS), which began to increase before puberty, continues to increase during puberty. Methods. The inclusion criteria included a diagnosis of idiopathic GHD, prepubertal on enrollment in the National Cooperative Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(8 citation statements)
references
References 8 publications
0
4
1
3
Order By: Relevance
“…compared studies between GHD and ISS patients on GH therapy of which one study reported a height gain of 1.3 SDS over an average of 4.6 years in patients with IGHD while another study reported a gain of only 0.5 SD in patients with ISS over an average of 4.4 years ( 24 ). Both the KIGS and NCGS GHD patient cohorts reported mean adult height SDS of -3.1 to 0.2 SDS ( 40 ) and -0.7 ± 1.3 ( 41 ) respectively, lower than our data after 8.1 years and 4.6 years respectively. Furthermore, Loche et al.…”
Section: Discussioncontrasting
confidence: 96%
“…compared studies between GHD and ISS patients on GH therapy of which one study reported a height gain of 1.3 SDS over an average of 4.6 years in patients with IGHD while another study reported a gain of only 0.5 SD in patients with ISS over an average of 4.4 years ( 24 ). Both the KIGS and NCGS GHD patient cohorts reported mean adult height SDS of -3.1 to 0.2 SDS ( 40 ) and -0.7 ± 1.3 ( 41 ) respectively, lower than our data after 8.1 years and 4.6 years respectively. Furthermore, Loche et al.…”
Section: Discussioncontrasting
confidence: 96%
“…Medical treatment of GHD (and all other approved indications for rhGH) entails daily subcutaneous injections. Early initiation of treatment and appropriate dosing can allow youths to achieve full growth potential (August, Julius, & Blethen, 1998;Mauras, Attie, Reiter, Saenger, Baptista, & the Genentech Inc. Cooperative Study Group, 2000).…”
Section: Medical and Psychoeducational Implicationsmentioning
confidence: 99%
“…3 It is likely that reduced adherence to daily injections limits treatment outcomes as evidenced by adult height in children who required GH replacement therapy that are below the mean for the population. [4][5][6][7][8][9][10] Maintenance of treatment adherence with daily GH (DGH) injections has also been shown to be problematic for adults with GHD because of device limitations, pain at injection sites, inconvenience of daily injections, lack of perceived immediate benefits, insurance barriers, and costs, leading to frequent dose omissions and treatment cessation. 11,12 Thus, it has been hypothesized that LAGH products might help mitigate treatment non-adherence and potentially improve long-term treatment effects in patients with PGHD and AGHD.…”
Section: Introductionmentioning
confidence: 99%
“… 3 It is likely that reduced adherence to daily injections limits treatment outcomes as evidenced by adult height in children who required GH replacement therapy that are below the mean for the population. 4–10 …”
Section: Introductionmentioning
confidence: 99%